Unmögliche Existenz! : ein Wort wider Karl Barth - Tügel, Franz, 1888-1946 1888-1946 (Agentur des Rauhen Hauses, 1933)
A booklet refuting Karl Barth's work, Theologische Existenz Heute!, Tügel was a Lutheran pastor and supported the régime of National Socialism.